O ato infracional como satisfação de necessidades do estômago e da fantasia: possuo, logo existo! - Silva, Mikaely Gonçalves da (2016)
This work has as object of study the motivation and condition to practice the offense by adolescents from João Pessoa County, establishing the relationship with the satisfaction of primitive needs of "stomach or fantasy." It is part of the premise that a need is an irresistible impulse that, somehow, it is impossible to be indifferent, ignore or resist. The needs are therefore inherent to the human condition; whether they are subsistence needs, consumer goods or affirmation before the group. This study involves the analysis of documents produced from the speech of teenagers, seeking to ascertain the principal acts committed infractions and how is the commission; explore the motivations for the practice of illegal acts and identify the teenage relationship / acts infractions / needs. It is a study that assumes that the capital ratio and work is done by means of establishing consensus processes and exploitation of the workforce, so that does not allow human emancipation, nor the satisfaction of needs socially constructed handicapping the maintenance of the members of the household; this context of denial of rights have impacts on social relationships of individuals and, in the case of adolescents in this study addressed, may lead them to meet their body or imaginary needs, through practices of infractions.